Das Interview : Grundlagen und Anwendung in Psychologie und Sozialwissenschaften /: Grundlagen und Anwendung in Psychologie und Sozialwissenschaften. (2020) - Renner, Karl-Heinz; Jacob, Nora-Corina
No abstract available